Investigating the effects of MWCNT-HB on gas storage performance of CO2 hydrate. (15th May 2022) - Liu, Ni; Meng, Fei; Chen, Litao; Yang, Liang; Liu, Daoping
Highlights: MWCNT-HB greatly improved the gas storage performance of CO2 hydrate. Secondary hydrate formation phenomenon in the MWCNT-HB system enhanced the gas storage capacity again. MWCNT-HB/SDS synergistically enhanced both heat and mass transfer processes during hydrate formation. Abstract: The technology of capturing CO2 using hydrate has attracted wide attention. In this study, the effects of two carbon nanomaterials, original multiwalled carbon nanotube (MWCNT) and modified herringbone carbon nanotube (MWCNT-HB), on the gas storage performance of CO2 hydrate were investigated under static conditions. Compared with the MWCNT system, the MWCNT-HB system showed a stronger ability to improve gas storage performance. Secondary formation of hydrate in the MWCNT-HB system was observed, and the final gas storage capacity could be increased by 119.2% compared to the pure water system. Due to the long stationary period between the two hydrate formation processes, MWCNT-HB was used in combination with tetrahydrofuran (THF) and sodium dodecyl sulfate (SDS) respectively. It was found that the MWCNT-HB/THF system inhibited the hydrate formation owing to a film formed on the suspension surface. In the MWCNT-HB/0.2% SDS system, the coupling effect of the two materials further enhanced the heat and mass transfer. The gas storage rate could reach 1.25 m 3 ·m −3 ·min −1, the gas storage capacity also increased to about 85 m 3 ·m − 3, and the induction time was only 5.1 min. The compound system not only enhanced the gas storage performance of CO2 hydrate but also effectively improved the phase equilibrium conditions. To further investigate the promotion mechanism, the thermal conductivity of the experimental materials, the surface tension of the solution, and the exothermic process of hydrate formation were measured and analyzed.